2003
DOI: 10.1130/g19754.1
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers, brines, and oil in the Mesoproterozoic, Roper Superbasin, Australia

Abstract: Gas chromatography-mass spectrometry of oil inclusions from the ca. 1430 Ma marine Roper Group in the Roper Superbasin, Australia, provides a new source of information about the early biosphere and Proterozoic petroleum systems. Oil most likely derived from an overlying shale was trapped at ϳ60 ؇C as abundant oil inclusions within transgranular microfractures in detrital quartz during Mesoproterozoic basin inversion. The oil is very mature and has a wide range of biomarkers, derived mainly from cyanobacteria, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 21 publications
5
38
0
Order By: Relevance
“…There are abundant acritarchs with ultrastructure and ornamentation indicative of eukaryotic affinities (Javaux et al, 2004). In support of this conclusion, kerogen and "live" oil from shales and fluid inclusions yield diverse sterane hydrocarbon biomarkers derived from eukaryotes (Summons et al, 1988;Dutkiewicz et al, 2003;Dutkiewicz et al, 2004;Volk et al, 2005;Siljeström et al, 2013; but see Flannery & George, 2014 for a contradictory finding), though most biomarkers are of prokaryotic origin. Sulfur isotope studies suggest that some of these prokaryotes metabolized by sulfate reduction (Donnelly and Crick, 1988) and sulfur disproportionation (Johnston et al, 2008).…”
Section: Roper Groupmentioning
confidence: 95%
“…There are abundant acritarchs with ultrastructure and ornamentation indicative of eukaryotic affinities (Javaux et al, 2004). In support of this conclusion, kerogen and "live" oil from shales and fluid inclusions yield diverse sterane hydrocarbon biomarkers derived from eukaryotes (Summons et al, 1988;Dutkiewicz et al, 2003;Dutkiewicz et al, 2004;Volk et al, 2005;Siljeström et al, 2013; but see Flannery & George, 2014 for a contradictory finding), though most biomarkers are of prokaryotic origin. Sulfur isotope studies suggest that some of these prokaryotes metabolized by sulfate reduction (Donnelly and Crick, 1988) and sulfur disproportionation (Johnston et al, 2008).…”
Section: Roper Groupmentioning
confidence: 95%
“…Steranes have been reported from a number of Proterozoic successions (e.g., Summons and Walter 1990;Dutkiewicz et al 2003) and are generally found in low abundance, reflecting at least in part the thermal maturity of their host rocks. These molecular fossils establish the presence of eukaryotes in Proterozoic oceans, but the scarcity of detailed records limits the inferences that can be drawn concerning ecological role or taxonomic affinities (because group-distinctive markers are generally below detection limits).…”
Section: Proterozoic Molecular Biomarkersmentioning
confidence: 99%
“…In contrast, the Roper and McArthur Basins of northern Australia contain rocks of low-to-moderate thermal maturity, more consistent with the probability of finding genuinely syngenetic biomarkers. Given that studies of the Roper and McArthur Basin sediments and oils consistently show the presence of steroids (Summons et al 1988a, b;Dutkiewicz et al 2003) along with other evidence for the in situ ) character of the bitumens, there seems little doubt that steroid biosynthesis operated as long ago as 1640 Ma. Preservation is a major limitation for both body and molecular fossil records at this point.…”
Section: Proterozoic Molecular Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative age of entrapment of FIs can be determined using textural relationships which, when coupled with a knowledge of the metamorphic and deformational history of the host rock, may constrain the potential sources. These tiny vessels are closed systems after entrapment and are shielded not only from contamination, but also from much of the alteration that usually affects other hydrocarbons over time [22][23][24] . Oil-bearing FIs have been shown to have been trapped during the Proterozoic and the Archaean [22,25] , and as such prove the contention that there was sufficient kerogen to form oil during thermal maturation [26,27] .…”
mentioning
confidence: 99%